Effect of tax Planning, Deferred Tax Charge, and Good Corporate Governance on Company Value With Profit Management as an Intervening Variable - Leni, Leni Hartati; Adriani Gunawan; Abdul Khoir (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study uses earnings management as an intervening variable to examine the effects of tax planning, deferred tax expense, and good corporate governance. Regression analysis was the study approach employed, and a sample of seventeen businesses in the textile and garment subsector that were listed on the Indonesia Stock Exchange between 2014 and 2021 was obtained using a purposive sampling technique. The research results demonstrate that while deferred taxes, profitability, and leverage have no appreciable impact on earnings management, good corporate governance and tax planning have a favorable and considerable impact. Additional findings indicate that firm value, deferred tax expense, and tax planning all significantly and favorably increase the value of a company. Earnings management, however, can not considerably mediating the impact of sound corporate governance and tax planing on firm value.